Marketing Tools in Modern Higher Education Institution: Tendencies of Research - I. V. Zakharova (Высшее образование в России)
The article addresses the problem of increasing competition in the markets of educational services, especially relevant for higher education, considers the stages and main problems of scientific research in the field of education marketing in the Russian Federation, analyzes the most significant works on the problems of economics and marketing of educational services. The article describes the University marketing complex, the composition and content of marketing activities in the markets of higher education. The article stresses the importance of social effects of an educational organization in assessing its competitive position and shows the organic nature of principles and technologies of relationship marketing as applied to educational organizations. Marketing methods for assessing the competitiveness of educational institutions and the demand for educational programs are of practical importance for higher education. The article substantiates the necessity of marketing management of educational organizations in modern conditions, as well as the need for higher education organizations to apply the principles of non-profit marketing. The author dwells on the approaches to the organization of University departments responsible for marketing functions. The marketing principles of educational organization are as follows: regular monitoring of educational market conditions, concentration of resources on those educational services that are relevant to economy development in appropriate market segments, the systematic decisionmaking, building long-term partnerships with educational services consumers. The author argues that there is an evolution of marketing functions in education – from situational use of marketing tools to the stage when management of educational institution is based on marketing principles, and marketing becomes management philosophy and defines corporate culture.